Analisis Level Keselamatan Kerja (K3) Proyek Konstruksi Terhadap Risiko dan Manajemen K3 (Studi Kasus : Proyek Pembangunan Terminal II Bandara Radin Inten II, Gedung Parkir Bandara Radin Inten II, Showroom Auto 2000) - milen, ayuma; Kustiani, Ika; siregar, amril (Universitas Lampung, 2016)
Whetherconstructionutilizingsimpleorcomplextechnology,theyarealwayspronetorisk of accidents.Applyingmanagementofoccupationalsafetyandhealthisveryimportantbecauseit cancreateagoodandsecureworkingenvironment.Howeverallitneedscommitmentfrom all stakeholdersto besuccessful. Thepurpose ofthisresearchistoassesthe implementationofsafetymanagementsystemin constructionprojects,identifyandquantifytheriskofaccidenteventsinconstructionprojects. Theresearchinvolvesquestionnairestogatherthemtheinformation. Therespondentscamefrom the projectcasesofstationII developmentRadinIntenIIairport,developmentofmulti-storeycar parkRadin Inten IIairport and developmentof auto 2000 showroom soekarno-hatta. This analysis was utilizing SPSS and the methode of analysis was frequency, validity and reliability test.Theresultsshowthatallthe threeprojectcaseshasamedium risk dueto accident causedbyignoring thesafetystandards and procedureareobvious. Keywords:Risk Management,Healthand SafetyEnvironment(SHE),SafetyManagement